Options to methane production abatement in ruminants: a review - J. Broucek (Journal of Animal and Plant Sciences, 2018)
The goal of this review was to analyze published data on practices that mitigate enteric methane (CH4) emissions from ruminants. The current approaches in relation to associated advantages and disadvantages and future options to reduce enteric CH4  emission are presented. Strategies for reducing ruminant CH4  output are considered in relationship to rumen ecology, biochemistry, and animal performance. The study is divided into nine sections (Defaunation and inhibition of archaea, Bacteriocins, Methane inhibitors and analogues, Probiotics, Saponins, Tanins, Ionophores, Organic acids, and Lipids). Defaunation or elimination of protozoa to reduce CH4 emission depending upon diet. Mitigation of CH4  emission by rumen microbes can be to apply the various chemicals. Some approaches such as immunization and chemical inhibitors directly target against their own rumen methanogens. Organic acids feeding promote propionate production. A reduction in CH4 production has also been observed with live yeast cells, lactate-utilizing bacteria, and by the selection of plant species that produce secondary metabolites, such as condensed tannins and saponins. Supplements rich in polyunsaturated fat acids such as linoleic acid, and linolenic acid also have a negative effect on CH4. Based on available results, it appears that dietary supplementation with fat or essential oils are the most promising dietary strategy.
Keywords: Environment; Methane; Ruminant; Additive